Interactive Educational Game for Chemistry in Virtual Reality with User Gesture Interactions via Smartwatches - Amaral, Lucas; Santos, Jamilly; Soares, Fabrizzio; Felix, Juliana; Cardoso, Luciana; Nascimento, Thamer Horbylon (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
This article explores a ludic approach to disseminating knowledge through a prototype of an interactive mobile virtual reality (mVR) game centered on chemistry education. Targeted at high-school students and chemistry undergraduates, with varying levels of prior knowledge, the game utilizes immersive experiences to encourage and facilitate learning. It discusses various interaction methods suitable for exploration-based mVR games, highlighting the integration of external devices like smartwatches. These devices enable dynamic ways of interaction via the continuous gesture recognition algorithm, enhancing user engagement and interaction within the virtual environment.